2022
DOI: 10.3389/fimmu.2022.934243
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of cellular senescence-related genes in the prognosis, tumor microenvironment, and immunotherapy/chemotherapy of clear cell renal cell carcinoma

Abstract: Background: The transcriptome public database and advances in biological discoveries contributed to significant progresses in identifying the drivers of cancer progression. Cellular senescence (CS) is considered as a leading factor resulting in cancer development. The purpose of this study was to explore the significance of CS-related genes in the molecular classification and survival outcome of clear cell renal cell carcinoma (ccRCC).Methods: CS-related genes were obtained from the CellAge database, and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrated that ccRCC is highly infiltrated by different immune cells and has high immune heterogeneity [ 98 , [101] , [102] , [103] ]. We found that high-risk patients had more plentiful immune and stromal components, lower tumor purity in the TME, and more abundant immunosuppressive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that ccRCC is highly infiltrated by different immune cells and has high immune heterogeneity [ 98 , [101] , [102] , [103] ]. We found that high-risk patients had more plentiful immune and stromal components, lower tumor purity in the TME, and more abundant immunosuppressive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (Wang et al, 2022) used the senescence-related gene set to define a cellular senescence score in pancancer and demonstrated that this score can represent the degree of immune activation in the tumor microenvironment and can identify groups with better prognosis. In specific cancers, researchers have also constructed classification models and prognostic prediction models based on senescence gene sets, including clear cell renal cell carcinoma (Lu et al, 2022), hepatocellular carcinoma (Luo et al, 2022), glioblastoma (Tan et al, 2022), etc., and explored the relationship between senescencerelated genes and clinical characteristics, tumor microenvironment, immunotherapy, etc. These studies demonstrate the importance of senescence genes in cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…By integrating these and other datasets developers performed a systems biology analysis of cell senescence. At present, there are few studies on CSRGs in ECa, but a number of studies have shown that CSRGs signature can play a prognostic role in hepatocellular carcinoma, gastric cancer, bladder cancer, renal cell carcinoma, and colon cancer (17)(18)(19)(20)(21). However, the expression characteristics and prognostic significance of CSRGs in ECa remain unclear.…”
Section: Introductionmentioning
confidence: 99%